Inmemoriam Dr Samten Tenzing - Badhu, Badri Prasad (Nepalese Journal of Ophthalmology, 2015)
This issue of the journal is dedicated to Dr SamtenTenzing. Born on 21st September 1961, Samten completed his secondary level education from the St Xavier’s School, Kathmandu. He was awarded a Colombo Plan Scholarship in 1981 to undergo his MBBS at the Rajendra Medical College, Ranchi University, India after which he joined the same college as an Honorary Junior Resident House Physician in the Department of General Medicine. He returned home and served at the Bir Hospital as a House Surgeon from December 1989 till July 1990.